Production, characterization, and potential utility of a newly synthesized allohexaploid wheat Triticum kiharae - Tariq Aslam; Tianying Zhang; Taotao Lian; Jiawen Zhai; Jinning Jia; Han Wang; Ruili Lyu; Bao Liu (Crop Journal)
Established allopolyploid species often contain specific gene(s) dedicated to suppressing the pairing of homoeologous chromosomes during meiosis. A longstanding question is whether such genes in allopolyploids with lower ploidy levels can retain full functionality when the ploidy level rises following the addition of a new subgenome during outcrossing. Here, we addressed this question by generating a synthetic allohexaploid wheat species, Triticum kiharae (GGAADD), by crossing the allotetraploid Triticum timopheevii (GGAA) to the diploid Aegilops tauschii (DD), followed by colchicine-induced chromosomal doubling. The gene Pairing homoeologous 1 (Ph1) inherited from T. timopheevii was likely hypofunctional in nascent T. kiharae, as evidenced by irregularities during meiotic chromosome pairing and organismal numerical and structural chromosome variation in selfed progeny populations. The allohexaploidization event also induced substantial rewiring of gene expression among homoeologs and nonadditive gene expression, leading to distinct predicted biological functions for differentially expressed genes (DEGs) when they were partitioned into the subgenomes. F1 hybrids from a cross between T. kiharae and bread wheat (T. aestivum, BBAADD) were male-sterile but female-fertile, confirming intrinsic postzygotic reproductive isolation between the two species while enabling backcrossing of these sterile F1 hybrids to bread wheat. These features provide a feasible route to simultaneously introgress standing congeneric genetic variations from both T. timopheevii and Ae. tauschii, as well as heritable de novo variations that have arisen in T. kiharae into bread wheat.